INCREASING THE STRENGTH OF CONCRETE MIXTURES (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In order to produce economically effective and environmentally safe superplasticizers for concrete mixtures in the construction industry and to obtain superplasticizers for concrete mixes based on pyrolysis oil in order to constantly improve existing technologies, as well as to adjust the structure formation processes of concentrated suspensions in the construction industry, the properties of finished products and initial It is vital to create new effective organic additives that can purposefully change the mobility of the mixture, physicomechanical, physicochemical properties of concrete mixes.